Romanticizing Life and Self Love between Phenomenon and Reality - Putri, Shevilla Chaerunisa; Wardhan, Nurullita Azka; Erawati, Dedet (PT FORMOSA CENDEKIA GLOBAL, 2024)
This form of romanticizing life aims so that we as weak humans can balance all the good and bad things that happen in our lives and that we can accept them well. This research uses qualitative methods with data collection techniques of observation, interviews, documentation and literature study using Sigmund Freud's communication psychology theory. This research was conducted to find out what methods are often used to romanticize each person's version of life. Based on the research conducted, it can be concluded that one form of romanticizing life can be done by carrying out positive creative activities such as bucket workshops. Through this activity they can express and give appreciation to themselves by creating work according to their own choice.